USE OF IDEAS AS MAKARENKO ON THE FORMATION OF PEDAGOGICAL CULTURE OF A TEACHER OF A MODERN SCHOOL - I.A. Mykytyuk (Academy of Cognitive and Natural Sciences, 2009)
The article is devoted to the research of the importance of creative legacy of A.S. Makarenko is the teaching process of High Educational Establishment. It is offered to consider development of education in a content of pedagogical culture.